Análise numérica do comportamento de escavações em solo grampeado: estudo de caso e influência dos condicionantes de projeto e de execução - Santos, Cauê Antônio Barreto da Rosa dos (2019)
This research presents numerical analyses considering excavations in nailed soil using the computational program Plaxis 2D. The numerical analysis was firstly validated against data from physical model study presented by Clouterre (1991). Parametric studies were then carried out to evaluate the combined effects of facing inclinations, excavations executed with and without niche, nail and facing stiffness, soil strength and stiffness parameter, surcharge conditions and excavation near the toe of the nailed structure. The results show that the increase of the facing inclination leads to higher values of connection and maximum reinforcement loads and greater horizontal facing displacements. In addition, the nail with highest load is located between the middle and the toe of the excavation, irrespective of the facing inclination. When the excavation is simulated by niches, the lateral movements are usually smaller, the tensile force carried by the connection is larger and the nail with highest load is closer to the toe of the excavation.